Detection of pure Leydig cell ovarian tumor not visible on imaging by selective venous blood sampling in a woman with secondary amenorrhea and hirsutism: A case report - Aki Oride; Haruhiko Kanasaki; Hiroe Okada; Satoru Kyo (Elsevier, 2021)
A 39-year-old woman (gravida 1, para 1) was referred to a university hospital with a high serum testosterone level and secondary amenorrhea, hirsutism, and weight gain. Her voice was deep, and hirsutism was observed on her chin, arms, and back. She also had clitoromegaly. Her serum testosterone levels were markedly elevated (testosterone 11.1 ng/mL, free testosterone 15.5 pg/mL). Transvaginal ultrasonography and magnetic resonance imaging did not reveal any tumors in the pelvic organs, including the uterus and ovaries. Enhanced computed tomography revealed no abnormalities in either adrenal gland. Blood sampling from the inferior vena cava, left renal vein, and the ovarian veins on both sides revealed an extremely high testosterone level (391 ng/mL) in blood from the right ovarian vein. Laparoscopic right oophorectomy was performed and the pathologic diagnosis was a Leydig cell tumor (1.5 × 1.5 × 1.3 cm). Her serum testosterone level decreased rapidly following oophorectomy (0.3 ng/mL on postoperative day 2). Her menstrual cycle had recovered spontaneously by 2 months after surgery and she noticed improvement in the hirsutism 4 months after the operation.